ATTEMPTED SYNTHESIS OF 5' - DEOXY - 5' - PHOSPHONO - ISOCYTIDINE SYNTHESIS OF PHOSPHONIC ACID DERIVATIVES OF ACYCLO - NUCLEOSIDES. PREPARATION OF 1- ?- D- ARABINOFURANOSYL PYRIMIDINES (Journal of Sciences, Islamic Republic of Iran)
The synthesis of 5' - deoxynucleoside 5' - phosphonates which contains a 5' - CP bond in place of the 5' -COP bond of the naturally occuring nucleotides is described. The preparation of phosphonate derivatives of acyclo - nucleosides and a simple method for the conversion of 1-? -D-ribofuranosyl pyrimidines to the corresponding 1-? -D-arabinofuranosyl pyrimidines are also explained